Synthetic and semi-synthetic antioxidants in medicine and food industry: a review - Jan Tauchen; Lukáš Huml; Michal Jurášek; Joe M. Regenstein; Fatih Ozogul; Fatih Ozogul (Frontiers in Pharmacology)
Oxidative stress is recognized as both a causative and contributing factor in many human diseases. As a result, significant research has been devoted to the development of synthetic and semi-synthetic antioxidants (ATs). This review summarizes the therapeutic potential of synthetic ATs, explores their possible clinical applications, and highlights novel structural modifications aimed at improving their pharmacological properties. Additionally, it presents ideas for refining current antioxidant testing methodologies. Despite the ongoing research, the therapeutic efficacy of synthetic ATs remains ambiguous for several reasons. These include the following: therapeutic benefits resulting from non-antioxidant mechanisms, insufficient dosage to elicit an antioxidant effect, poor oral bioavailability, a narrow therapeutic index, or toxicity that precludes clinical use. Nevertheless, some compounds, such as ebselen, edaravone, MitoQ10, and potentially N-acetylcysteine, have shown promising results. However, further studies are needed to confirm their efficacy and clarify whether their therapeutic effects are truly mediated through antioxidant mechanisms. Dietary antioxidants have achieved relatively higher clinical success, although their toxicity has also led to the withdrawal of some agents. One emerging therapeutic strategy involves inhibition of NADPH oxidase (NOX) enzymatic activity, with compounds such as ebselen, S17834, and GKT137831 showing potential across various disease models. Efforts to enhance antioxidant properties through molecular modifications, using advanced technologies such as prodrug strategies, nanotechnology, polymer complexation, targeted delivery systems, or conversion into inhalable formulations, have yielded variable success. Still, confirming the clinical relevance of newly developed antioxidants will require a paradigm shift in the testing approaches. Future studies must better define the molecular context of antioxidant action, including the following: which biomolecules are being protected, the specific radical species targeted, the tissue and subcellular distribution of the antioxidant, and how levels of endogenous antioxidants and reactive oxygen species (ROS) change post-administration (e.g., within the mitochondria). Despite extensive research, only a few synthetic antioxidants, such as edaravone, are currently used in clinical practice. Currently, no new antioxidant drugs are expected to receive regulatory approval in the near future.